SPECIFICS OF ARTERIAL HYPERTENSION COURSE IN PATIENTS WITH AORTIC ATHEROSCLEROSIS COMPLICATED BY ACUTE THROMBOTIC OCCLUSION - E. М. Evsikov; N. V. Teplova; D. A. Maytesian; R. A. Sharipov; М. Kh. Zhapueva; N. N. Levchuk; V. V. Kashirin; G. А. Chervyakova; Е. G. Kurumlidu; S. А. Abduragimov (Российский кардиологический журнал)
Aim. To evaluate the main possible reasons for arterial hypertension in patients with thrombotic occlusion of the large arteries of extremities in atherosclerotic disease.Material and methods. The course of arterial hypertension was analyzed in 129 cases of atherosclerotic aortic disease, complicated with acute thrombotic occlusion of the arteries of lower (112) and upper (17) extremities due to thrombosis (108) and embolism (21) of magistral vessels comparing to the data of 46 patients with chronic ischemia of lower extremities.Results. Arterial hypertension (AH) in anamnesis was marked in all patients of study groups and comparison group. systolic AH was diagnosed in 17,8% (23), and in comparsion group — 19,5% (9). Thrombectomy was followed by the decrease of mean BP in most of patients, with good effect of operation and return of adequate circulation in the extremity — in 82,2%, by mean 17,1% systolic and 21,4% — diastolic BP. In 31 patient the dynamics of systolic and diastolic BP after operation was not single-directed and did not raise for more than 5% over baseline, and in 7% cases there was increase of BP, by mean 19,4% systolic and 22,6% diastolic. GFR levels were lower than normal in more than 70% patients of AEI and more than 65% in comparison group.Conclusion. Thrombectomy and reconstruction interventions on occluded arteries, with successful restore of main circulation in the extremity, are followed by significant decrease of systemic systolic and diastolic arterial pressure in most patients.